Aplikasi Rekomendasi Resep Menu Meal Plan Berdasarkan TDEE dan Zat Gizi Makro Pengguna Berbasis Web Dengan Pendekatan MCDA Dan EgoSimilar+ - Ivana Jovita Handoko; Henry Novianus Palit; Liliana Liliana (Universitas Kristen Petra, 2022)
Public awareness in Indonesia of the importance of a healthy lifestyle is getting higher today. Having a healthy and ideal body is the dream of people in Indonesia. One way to achieve a healthy and ideal body is to control the intake of calories, carbohydrates, protein and fat in the food consumed (TDEE and macronutrients). Everyone has different needs for TDEE and macronutrients. It is difficult to meet macro needs in accordance with the daily calorie TDEE if you do not understand how to arrange a daily food menu. TDEE and macronutrients should not be lacking nor should they be in excess, while the composition of each macro has a different calorific value for each gram unit in each food ingredient.The meal plan menu recommendation system uses EgoSimilar+ and AHPSort which is the MCDA approach, the method used in this study is used to build the